Evaluation of capacities of bucket foundations in soft-stiff-soft clays under combined loading - Yang, Ningxin; Zhou, Mi; Tian, YInghui; Zhang, Xihong (Elsevier, 2021)
Bucket foundations are widely constructed for offshore wind turbines, which are subjected to combined vertical-horizontal-moment (V-H-M) loading during operation. This technical note presents an extensive investigation into the response of bucket foundations in soft clay interbedded with a stiff clay layer (or soft-stiff-soft clays) under combined loading, which is a supplement to the existing design specification. The numerical method employed in this study is validated by comparing the bearing capacities of bucket foundations with previously published data. The numerical modeling results from this study show that the failure mechanism of bucket foundations in soft-stiff-soft clays under combined loading is significantly different from that in single-layer soft clay condition. A series of numerical analyses are conducted to explore the effects of geometric variation with the interbedded stiff clay, soil material properties and combined loading onto the bearing capacities of bucket foundations. Based on the parametric studies, a new failure mechanism for bucket foundations in soft-stiff-soft clays under general loading is obtained. And a corresponding design method is established, which can be used to calculate the monotonic vertical, horizontal, and moment bearing capacities, as well as the capacity envelopes under combined loading.